St. Louis, Mo., Rev. Ordinances ch. 20, art. 2, § 9 (1871) - (:unkn) unknown (My University, 1871)
Ordinances of the City of Saint Louis, Misdemeanors, § 9: Hereafter it shall not be lawful for any person to wear under his clothes, or concealed about his person, any pistol, or revolver, colt, billy, slung shot, cross knuckles, or knuckles of lead, brass or other metal, bowie knife, razor, dirk knife, dirk, dagger, or any knife resembling a bowie knife, or any other dangerous or deadly weapon, within the City of Saint Louis, without written permission from the Mayor
Keywords: CARRY - CONCEALED